Investigating the content of microplastics and other extraneous particles in Polish bottled water - Aleksander-Kwaterczak, Urszula; Gaj, Dominika; Stelmach, Alex; Wróbel, Tomasz P. (Geology, Geophysics and Environment, 2023)
Bottled water has enjoyed a global increase in popularity since it is generally perceived to be superior in quality to tap water and necessary when tap water is non-potable. As a result, ensuring that it meets the requisite quality standards is of vital importance. This work aims to examine the content of solid particles, including microplastics, in bottled water available in Polish stores. The second aspect is the preliminary determination of the influence of the water gassing process, together with thermal and light factors, on the content of particles in the water. The number of particles was counted by colour and shape, with the number ranging from 87 to 188 per litre of water; on average, there were 136 ±32 particles per litre of water, demonstrating that water from disposable plastic bottles is contaminated with various substances. The difference in the number of particles may be due to the origin of the waters, the processes they were subjected to prior to bottling, the properties of the bottles as packaging, and the conditions and length of storage and transport. Additional Fourier-transform infrared spectroscopy (FT-IR) analysis confirmed that about 75% of the particles were polymers, and 50% of them were plastics. Particularly alarming is the fact that the bottled waters mostly contained microplastic particles (MP) of smaller sizes, the kind which is recognized as being the most dangerous to human health. In the study, most particles were in the form of irregular shapes, which may indicate that they come from the destruction of waste or plastic products. This is also indicated by the domination of colourless particles. More particles were found in waters exposed to high and low temperatures than in waters stored at room temperature, potentially indicating that storage conditions for drinking water are important. Taking into account the results obtained, increasing attention should be paid to the health risks posed by such microplastics and there is a clear need to introduce legal regulations on the matter. The lack of any legal guidelines or unified standards in the field of MP research means that the results are not always representative, and it also makes it difficult to compare the results from different studies.